Meeting basic physical-biomedical needs of children under 5 years; does the family hope program work? - Fauziyah Fauziyah; Ni'mal Baroya; Christyana Sandra (Alma Ata University Press, 2024)
Background: fulfillment of the basic physical biomedical needs of children under five affects their growth and development. Most poor families pay little attention to the basic needs of their children due to lack of knowledge and the economy. To overcome this, the Ministry of Social Affairs of the Republic of Indonesia has issued social security to reduce the number of poverty and social welfare cases called the Family Hope Program (PKH). Within the health sector, KPM (Beneficiary Families) are required to ensure the provision of fundamental healthcare services for children under the age of five. These services include monthly regular vaccines, biannual administration of Vitamin A, and monthly monitoring of the children's weight. Objectives: this study aims to analyze the impact of conditional cash transfer programs on the fulfillment of basic physical-biomedical needs. Methods: we conducted a quantitative study using a cross sectional design. Our research sample was 83 of 289 children under five years in Patempuran-Kalisat-Jember taken using simple random sampling technique. Results: the results showed that there were no differences in the completeness of immunization (Sig = 0.501), exclusive breastfeeding (Sig = 0.378), routine weighing (Sig = 0.445) and utilization of health services (Sig = 0.845) between conditional cash transfer program recipients and non recipients. Conclusions: This program is considered effective because the majority of children under five have received complete basic immunization and routinely have their weight weighed at the posyandu, but children under the age of five are not given exclusive breast milk. The social service and primary health care need to increase collaboration to provide education about the importance of exclusive breastfeeding.